Uji Efektivitas Pemanfaatan Biji Pepaya (Carica Papaya L) Kering Dan Basah Sebagai Larvasida Alami Cair Untuk Mematikan Larva Aedes Aegypti - Rachman, Erwinda Alwi; Juherah, Juherah; Ismawati, Ismawati (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Scarlet fever or dengue fever is an infectious disease in the tropics area that is caused by the dengue virus and transmitted by the Aedes aegypti mosquito One of the plants which can be utilized as natural larvicide is papaya seeds (Carica papaya L). The wet and dry papaya seeds are used in this research. The papaya seeds contain toxic compounds, they are alkaloids, flavonoids, saponins, and tannins. These compounds can inhibit the growth of Aedes aegypti larvae. This research is quasi-experimental. It aims to find out the effectiveness of the dry and wet papaya (Carica Papaya L) seed solvents with doses of 20 ml / Litre, 30 ml / Litre, 40 ml / Litre 50 ml / Litre, and 60 ml / Litre. The control was exposed to 20 Aedes aegypti larvae at each dose with observations every 60 minutes for 24 hours with the time intervals, the replication was carried out three times.The result shows that the mortality rate of Aedes aegypti larvae in the solvents of dry papaya seeds is the control no one dies (0%) doses of 20 ml can turn off (95%), 30 ml can turn off (100%), 40 ml can turn off (100%), 50 ml can turn off (100%), 60 ml can turn off (100%), , meanwhile, the solvents of wet papaya seeds are the control no one dies (0%) doses of 20 ml can turn off (100%), 30 ml can turn off (100%), 40 ml can turn off (100%), 50 ml can turn off (100%), 60 ml can turn off (100%). In a conclusion, a dose of 20 ml is the most effective dose as a liquid to kill Aedes aegypti larvae. Sugestions for the public to use wet papaya seeds as larvicide and for future researchers to use a dip bag and the dose used can be lowered by using wet papaya seeds. Keywords : Aedes aegypti Larvae, Papaya Seeds (Carica Papaya L)